Interfering substances in the analysis of patient serum samples with dialysis by chloride ion-selective polymeric membrane electrodes based on methyltridodecylammonium salt - SHIBATA, Yasuhisa; HIROTA, Kunio; MIYAGI, Hiroyuki; TAKATA, Yoshinori (BUNSEKI KAGAKU, 1993)
Interference in the analysis of undiluted patient serum samples with dialysis by chloride ion-selective polymeric membrane electrodes (Cl-ISEs) was studied. The sensing membrane of Cl-ISE was prepared by using methyltridodecylammonium salt and 1-tetradecyl alcohol as a sensing material and a plasticizer, respectively. In the case of new Cl-ISE, fast response and good correlation to the reference method (chloride counter) were obtained. On the other hand, the used Cl-ISE showed slower response to the patient serum samples with dialysis compared to standard solutions and patient serum samples without dialysis. In many cases, the analytical values of patient serum samples with dialysis by used Cl-ISE were 10 mmol/l or more higher than that of chloride counter. It was shown that the new Cl-ISE had changed to become easily responsive to lipophilic anions and organic acid compounds after the immersion in control serum samples. The patient serum samples with dialysis were analyzed by the gel permeation chromatog-raphy(GPC) using a UV detector and many peaks which could not be observed in the measurement of patient serum samples without dialysis were detected. The used Cl-ISE was applied to the detector of GPC and the patient serum samples with dialysis were analyzed. Two peaks (retention time: 12.4 and 16.4 min) based on the compounds whose molecular weights are larger than Cl- (retention time: 18.8 min) were observed. The used Cl-ISE covered the surface of sensing membrane with dialysis membrane (fractional molecular weight: 1000) was applied to the detector of GPC and no peak was observed. Therefore, it was suggested that the molecular weights of interfering substances in patient serum samples with dialysis were over 1000.